Midodareni dalam Perspektif Sakramen Perkawinan Gereja Katolik - Maharani, Skolastika Dinda Ayu; Sakti X, Pius Intan; Tarihoran, Emmeria (Perspektif, 2025)
As a student of Catholic Religious Education, the author views Midodareni as one of the Javanese cultural heritages that contains spiritual and moral values in harmony with the teachings of the Catholic faith. This tradition is carried out on the night before marriage as a form of prayer and a request for blessings for the bride and groom. Through a descriptive qualitative study based on library research, this paper aims to explore the theological meaning and relevance of the Midodareni tradition in the light of the Catholic sacrament of marriage, as well as to highlight how the process of faith inculturation takes place in the lives of Catholics in Java. The findings show that Midodareni is not merely a cultural ritual but a living expression of faith, where the values of holiness, fidelity, prayer, and hope in God’s grace form its central meaning. The Catholic Church, through the spirit of inculturation, values local culture as a means of bringing the Gospel into the life of the community without diminishing the truth of faith. As a future Catholic religious educator, reflecting on this tradition fosters an awareness that the proclamation of faith cannot be separated from the cultural context of the faithful. Therefore, understanding Midodareni is not only an effort to preserve culture but also a concrete form of faith education that is contextual and rooted in the values of humanity, love, and God’s salvation.